PEMANFAATAN POTENSI SUMBER AIR SEBAGAI PILAR UTAMA KETAHANAN PANGAN DI DESA MOTONGBANG - Juliana Albertina Mayopu; Inggrit Elisabet Bayang; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to describe the utilization of water resources as a key pillar of food security in Motongbang Village, Teluk Mutiara District, Alor Regency. This village has two main water sources, namely a river spring and a drilled well (PAM), which are used for domestic, agricultural, and livestock needs. The research method used is a qualitative method with a descriptive approach through field observations and interviews with village officials. The results show that the river spring is the main water source for the community because its flow is stable, the water is clear, and it is easily accessible at no cost. Meanwhile, the drilled well serves as a supporting source, especially during the dry season and for areas far from the river flow. The availability of clean water has been proven to support the agricultural and livestock sectors, which are the largest livelihoods of the community, with 106 people working in the agricultural sector and 95 people in the livestock sector. Adequate clean water potential allows the community to increase land productivity, raise livestock, and ensure water needs for households. Thus, water resources in Motongbang Village play a significant role in strengthening food security and the welfare of the village community.